Menyingkap Simbol Kematian dalam Cerpen Der Tunnel Karya Friedrich Dürrenmatt: Analisis Hermeneutika Paul Ricoeur - Deireadh Farroza Malana; Isti Haryati (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA (JBSP), 2026)
This study aims to describe the symbols of death represented in Friedrich Dürrenmatt's short story entitled Der Tunnel from the perspective of Paul Ricoeur's hermeneutics. The research data source includes the 2021 edition of Friedrich Dürrenmatt's short story entitled Der Tunnel, which was first published in 1952. The research method used is descriptive qualitative with a hermeneutical approach based on Paul Ricoeur's hermeneutics. The results show that there are fifteen forms of death symbols with seventy occurrences from fifty quotations in the text. The dominant symbol depicts the journey of life toward death, followed by general symbols of death, tradition, awareness, unconsciousness of death, self-destruction, and existential alienation. Through Ricoeur’s perspective, the findings suggest that Dürrenmatt uses these symbols to highlight human limitations in the face of an absurd destiny. This research contributes to the field of literary studies by demonstrating how hermeneutic interpretation transforms a literary text into a medium for philosophical reflection on transience and the essence of human existence in a modern, alienated world.